Perioperative management of polycythemia vera with advanced gastric cancer: A case report. (2019) - Mochizuki, Tetsuya; Tanabe, Kazuaki; Saito, Ryusuke; Ota, Hiroshi; Yamamoto, Yuji; Saeki, Yoshihiro; Ohdan, Hideki
Highlights: We report a case involving operation for gastric cancer after treatment for PV. Control of WBC and Plt counts during the perioperative period led to good results. Perioperative management for PV is important for complication-free surgery. Careful follow up should be performed for gastric cancer and PV recurrence. Abstract: Introduction: Polycythemia vera (PV) is a chronic myeloproliferative disorder with generally good prognosis. However, thrombotic and cardiovascular complications are among the leading causes of death in patients with PV and sufficiently effective management strategies are yet to be established. We report a case involving operation for gastric cancer in a patient being treated for PV. Presentation of case: A 73-year-old man was diagnosed as PV on the basis of abnormal laboratory data eight years previously. Three months ago, he was referred to our department for anorexia and melena. The preoperative diagnosis was advanced gastric cancer, Stage IIB. To avoid perioperative thrombotic and hemorrhagic events, low-dose aspirin administration was continued with an additional dose of hydroxyurea. Emergent control was necessary because of the severity of gastric cancer symptoms, including pyloric stenosis and anemia. Distal gastrectomy with D2 lymph node resection was performed. The postoperative course was satisfactory, and the patient is currently doing well without any signs of recurrence or hematological complications. Discussion: We described the successful management of a patient being treated for PV who underwent gastrectomy. As mentioned earlier, thrombotic complications and hemorrhage during the perioperative period are the major risk factors in patients with PV. In this case, control of white blood cell and platelet counts during the perioperative period led to good results. Conclusions: Perioperative management for PV is important for complication-free surgery. Careful follow up should be performed for gastric cancer and PV recurrence.